2007
DOI: 10.1007/s00247-007-0599-6
|View full text |Cite
|
Sign up to set email alerts
|

US findings of adnexal torsion in children and adolescents: size really does matter

Abstract: An adnexal volume of <20 ml is strong evidence against adnexal torsion in menarchal females. In this age group, the diagnosis of torsion cannot be established by US examination alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 17 publications
1
59
0
Order By: Relevance
“…Color Doppler sonography proposed to improve accurate diagnosis [18] has not been used in the present series. Linam et al [19] demonstrated that Doppler findings have low sensitivity and specificity for diagnosing ovarian torsion.…”
Section: Discussionmentioning
confidence: 99%
“…Color Doppler sonography proposed to improve accurate diagnosis [18] has not been used in the present series. Linam et al [19] demonstrated that Doppler findings have low sensitivity and specificity for diagnosing ovarian torsion.…”
Section: Discussionmentioning
confidence: 99%
“…A study by Linam et al [19] also found that ovarian size is a good predictor of torsion. In their series, no ovarian torsion was present in ovaries that were less than 20 ml and the best predictor of torsion was a volume ratio with the normal ovary of 15 [19]. Finally, a recent case report has shown that although very uncommon, even normal ovarian volume and volume ratios can be present in patients with ovarian torsion [20].…”
Section: Ultrasoundmentioning
confidence: 91%
“…When the median ovarian volume ratio was 20 or more, patients were 18 times more likely to have an associated underlying ovarian mass [1]. A study by Linam et al [19] also found that ovarian size is a good predictor of torsion. In their series, no ovarian torsion was present in ovaries that were less than 20 ml and the best predictor of torsion was a volume ratio with the normal ovary of 15 [19].…”
Section: Ultrasoundmentioning
confidence: 96%
See 1 more Smart Citation
“…The diagnosis of ovarian torsion relies on history, clinical findings, and supportive imaging. The most common ultrasound finding is an enlarged ovary [8]. Other findings include absence of Doppler flow, peripheral follicles of 8 to 15 mm with fluid debris levels, free intraperitoneal fluid, thickening of cyst wall, and whirlpool sign [5,[9][10][11].…”
Section: Commentsmentioning
confidence: 99%